2022
DOI: 10.25071/1920-7336.40937
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothers Behind the Scenes

Abstract: Research and policy concerning the Syrian Canadian diaspora has not prioritized elders. This article adds to scholarship about the well-being of newcomers admitted via the Syrian Refugee Resettlement Initiative through a focus on grandmothers resettled within their multigenerational families. Using interviews and qualitative field research, we show how the authority and status these elder women once held in Syria may be undermined by their comparatively subordinate integration in Canada. Although new, post-mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Of the five studies that apply a longitudinal design, on average the study follow-up period is 3.3 years. The longest study follow-up period was 6 years [18], while the shortest follow-up period was 6 months, with assessments occurring 3 to 5 months following the baseline assessment [19]. More detailed information is presented in Table 1.…”
Section: Methods and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the five studies that apply a longitudinal design, on average the study follow-up period is 3.3 years. The longest study follow-up period was 6 years [18], while the shortest follow-up period was 6 months, with assessments occurring 3 to 5 months following the baseline assessment [19]. More detailed information is presented in Table 1.…”
Section: Methods and Study Designmentioning
confidence: 99%
“…For example, two studies reported participants were 18 years and over [23,24]. One study recruited only elders aged 60 years and older [18]. The majority of studies (58.1%, n = 25) recruited both male and female participants.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation